A methodological validation of an easy one‐step swimout semen preparation procedure for selecting DNA fragmentation‐free spermatozoa for ICSI. (28th October 2020) - De Gheselle, Stefanie; Deroose, Aurelie; Stevens, Jani; Hiel, Margaux; Tilleman, Kelly
Abstract: The main purpose of this methodological paper was to describe a recently designed one‐step ICSI semen preparation swim‐out method (called swim‐ICSI) and to compare its efficacy with our conventional two‐step swim‐out method for the selection of motile spermatozoa for ICSI with minimal DNA damage. In this observational cohort study, 42 fresh ejaculate sperm samples for ICSI were included to compare the new swim‐ICSI with the conventional swim‐out. In a sub‐analysis ( n = 20), both in‐house designed ICSI preparation methods were compared with a commercial magnetic‐activated cell sorting test (MACS ® ). Sperm DNA fragmentation (SDF), using Halosperm ®, was determined at different time points during sperm preparation: on the native sample (a), after density gradient centrifugation (DG) (b), on the motile (A + B) spermatozoa selected with conventional swim‐out post‐DG (c) and selected with swim‐ICSI method post‐DG (d). For a subgroup ( n = 20), SDF was also calculated after MACS (e). The mean SDF significantly reduced after EACH preparation step and reduced to almost zero in the recovered A + B spermatozoa when the semen prepared with DG was further processed for ICSI (swim‐ICSI vs. swim‐out, p = .001). In conclusion, the optimised one‐step and fine‐tuned swim‐ICSI technique shows the possibility to select a population of spermatozoa with almost zero SDF to be used in ICSI treatments.